Implementing the Endangered Species Act on the Platte Basin water commons - Freeman, David M. (University Press of Colorado, 2010)
Water users of the Platte River Basin have long struggled to share this scarce commodity in the arid high plains, ultimately organizing collectively owned and managed water systems, allocating water along extensive stream systems, and integrating newer groundwater with existing surface-water uses. In 1973, the Endangered Species Act brought a new challenge: incorporating the habitat needs of four species-the whooping crane, piping plover, least tern, and pallid sturgeon-into its water-management agenda.